Pengaruh Terapi Bermain Gelembung Super Terhadap Tingkat Kecemasan Pada Anak Usia Prasekolah Yang Mengalami Hospitalisasi - Sari, Diah Luki Yunita; Arifah, Siti (Jurnal Berita Ilmu Keperawatan, 2017)
Children who are hospitalized will easily experience crises and problems such as anxiety. One way to reduce anxiety is to provide super bubble play therapy. The purpose of this study was to determine the effect of super bubble play therapy on anxiety levels in preschool children. The method used was a pre-experimental type of one group posttest. The sample used was children aged between 4 to 5 years (preschool age) who had been hospitalized in Pandan Arang Boyolali Regional Hospital during the past month, namely 16 children and had undergone hospitalization on the second day using accidental sampling techniques and using t-test. The results showed that there was an influence of super bubble play therapy on the level of anxiety in preschoolers who were hospitalized in the Children's Room of Pandan Arang Boyolali Regional Hospital (p = 0,000). The conclusion of this study is that there is an influence of super bubble play therapy on the level of anxiety in preschool children who are hospitalized in the Children's Room of Pandan Arang Boyolali Regional Hospital